Reliable words; Third person pronouns in Indonesian News Reports - Djenar, Dwi Noverini (Wacana, Journal of the Humanities of Indonesia, 2010)
This article examines uses of Indonesian third person singular pronouns ia and dia in news reports. It takes as its departure point the general account of the pronouns which specifies that ia can occur only in subject position, while dia can occur in subject or object position. The article shows that, although both pronouns can occur in subject position, they differ distributionally and functionally. Ia occurs almost three times as frequently as dia and predominates in subject position, while dia occurs mostly in non-subject position. Ia is primarily used to convey the notion that the referent is a reliable and authoritative source of information and to focus on the referent as an agent or protagonist who is initiating or performing some action or a series of actions. By contrast, dia tends to be selected for contexts in which the referent is presented as a speaker who is elaborating on what has been said previously rather than introducing a new point. The predominance of ia in news report accords with its characterization as a pronoun strongly associated with formal registers.